MEMBANGUN KEBERAGAMAN DI SEKOLAH INKLUSI MELALUI PENDIDIKAN MULTIKULTURAL - Nurkholifah, Siti; Zakiah, Linda; Adiesty, Jasmine; Aziz, Abdillah; Jaya, Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Multicultural education plays a vital role in Indonesia., a country with a lot of diversity. Multicultural education emerged with the aim of fighting discrimination, prejudice, or conflict due to misunderstanding or intolerance towards differences. The research aims to explore how multicultural education contributes to the development of diversity in inclusive schools. A literature study methodology is used in this study with secondary data in the form of books, articles, journals, and other documents as research sources. The results are prepared using the principle of simplicity in order to facilitate the reader's comprehension. This research shows that in an inclusive school environment, multicultural education plays a crucial role in building awareness, appreciation, and tolerance for student diversity. By strengthening students' characters and creating an inclusive learning environment, multicultural education can help overcome stereotypes, prejudices, and intercultural conflicts.